Management of post traumatic posterior acetabular labral tear: a case report - Kulkarni, Shrihari L.; Daragad, Manjunath; Patil, Arvind D.; Patil, Naveenkumar; Nuhman, Mohammed (International Journal of Research in Orthopaedics, 2022)
Traumatic acetabular labral tears causing hip instability are rare. Surgical management of posterior labral tear is essential to prevent chronic hip instability and secondary arthritis. We report a 27-year-old female presented following RTA, with posterior hip dislocation along with posterior labral avulsion, managed by surgical repair using suture anchors. Patient had excellent functional outcome at 12 months of follow-up. High index of suspicion for labral injuries is required in patients with posterior hip dislocation and posterior wall fractures. Early surgical repair of torn labrum is must for excellent functional outcome.